2017
DOI: 10.1016/j.cognition.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of utterance timing and stimulation of left prefrontal cortex on the production of referential expressions

Abstract: We examined the relationship between the timing of utterance initiation and the choice of referring expressions, e.g., pronouns (it), zeros (…and went down), or descriptive NPs (the pink pentagon). We examined language production in healthy adults, and used anodal transcranial direct current stimulation (tDCS) to test the involvement of the left prefrontal cortex (PFC) on the timing of utterance production and the selection of reference forms in a discourse context. Twenty-two subjects (11 anodal, 11 sham) des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…If so, the given status of the goal characters may be stronger than the given status of source characters, leading speakers to choose acoustically reduced expressions more often for goals. To our knowledge, no existing theories of information status propose that attention to the discourse context can vary, but this idea is consistent with other recent work from our lab (Arnold & Nozari, 2017;Zerkle & Arnold, in press). …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…If so, the given status of the goal characters may be stronger than the given status of source characters, leading speakers to choose acoustically reduced expressions more often for goals. To our knowledge, no existing theories of information status propose that attention to the discourse context can vary, but this idea is consistent with other recent work from our lab (Arnold & Nozari, 2017;Zerkle & Arnold, in press). …”
Section: Discussionsupporting
confidence: 91%
“…Unlike Experiment 1, we found that connective use did predict duration, in that the presence of a connective led to longer durations. This effect is somewhat surprising, in that other studies have found that connectives co-occur with the choice of lexically reduced expressions like pronouns (Arnold & Griffin, 2007;Arnold & Nozari, 2017). In the current task, the connective may have been used as a mechanism for gaining additional time to prepare the utterance.…”
Section: Experiments 2 Summarymentioning
confidence: 88%
See 2 more Smart Citations
“…There is both behavioral and neural evidence that resolving such competition requires executive control (Shao, Meyer, & Roelofs, 2013; Shao, Roelofs, & Meyer, 2012; Schnur et al, 2009). At the sentence level too, accuracy and timing of processing have been shown to depend on executive control abilities and their neural correlates, especially the left lateral prefrontal cortex, in both sentence comprehension (Nozari, Mirman, & Thompson-Schill, 2016; Nozari, Trueswell, & Thompson-Schill, 2016) and sentence production (Arnold & Nozari, 2017; Nozari, Arnold, & Thompson-Schill, 2014; see Nozari & Thompson-Schill, 2015 for a review).…”
Section: Discussionmentioning
confidence: 99%